Empathy among medical students: is there a relation with quality of life and burnout? - Helena B M S Paro; Paulo S P Silveira; Bruno Perotta; Silmar Gannam; Sylvia C Enns; Renata R B Giaxa; Rosuita F Bonito; Mílton A Martins; Patricia Z Tempski (PLoS ONE)
Background We aimed to assess medical students' empathy and its associations with gender, stage of medical school, quality of life and burnout. Method A cross-sectional, multi-centric (22 medical schools) study that employed online, validated, self-reported questionnaires on empathy (Interpersonal Reactivity Index), quality of life (The World Health Organization Quality of Life Assessment) and burnout (the Maslach Burnout Inventory) in a random sample of medical students. Results Out of a total of 1,650 randomly selected students, 1,350 (81.8%) completed all of the questionnaires. Female students exhibited higher dispositional empathic concern and experienced more personal distress than their male counterparts (p<0.05; d ≥ 0.5). There were minor differences in the empathic dispositions of students in different stages of their medical training (p<0.05; f<0.25). Female students had slightly lower scores for physical and psychological quality of life than male students (p<0.05; d<0.5). Female students scored higher on emotional exhaustion and lower on depersonalization than male students (p<0.001; d<0.5). Students in their final stage of medical school had slightly higher scores for emotional exhaustion, depersonalization and personal accomplishment (p<0.05; f<0.25). Gender (β = 0.27; p<0.001) and perspective taking (β = 0.30; p<0.001) were significant predictors of empathic concern scores. Depersonalization was associated with lower empathic concern (β =  -0.18) and perspective taking (β =  -0.14) (p<0.001). Personal accomplishment was associated with higher perspective taking (β = 0.21; p<0.001) and lower personal distress (β =  -0.26; p<0.001) scores. Conclusions Female students had higher empathic concern and personal distress dispositions. The differences in the empathy scores of students in different stages of medical school were small. Among all of the studied variables, personal accomplishment held the most important association with decreasing personal distress and was also a predicting variable for perspective taking.